A Critical Examination of the Practical Implications Derived from the Food Addiction Concept - Meule, Adrian (Curr Obes Rep, 2019)
PURPOSE OF REVIEW: Adopting an addiction perspective on eating disorders and obesity may have practical implications for diagnostic classification, prevention, and treatment of these disorders. The present article critically examines these implications derived from the food addiction concept. RECENT FINDINGS: Introducing food addiction as a new disorder in diagnostic classification system seems redundant as most individuals with an addiction-like eating behavior are already covered by established eating disorder diagnoses. Food addiction may be a useful metaphor in the treatment of binge eating, but would be inappropriate for the majority of obese individuals. Implying an addiction to certain foods is not necessary when applying certain approaches inspired by the addiction field for prevention and treatment of obesity. The usefulness of abstinence models in the treatment of eating disorders and obesity needs to be rigorously tested in future studies. SUMMARY: Some practical implications derived from the food addiction concept provide promising avenues for future research (e.g., using an addiction framework in the treatment of binge eating or applying abstinence models). For others, however, the necessity of implying an addiction to some foods needs to be scrutinized.